Transformasi Pembelajaran Before-After Pandemi Covid-19 Pada Madrasah Diniyah Raoudlotul Muttaqin Di Desa Dero, Kecamatan Bringin, Kabupaten Ngawi - Khoiruddin, Untung (JoIEM (Journal of Islamic Education Management), 2021)
This article discusses the transformation process of Islamic learning at the Madrasah Diniyah Roudlotul Muttaqin which located in Dero Vilage-Ngawi Regency. By using descriptive qualitative method, interview and deep observation, this research will review in depth various data and information that urgen and related. Madrasah Diniyah Roudlotul Muttaqin is an Islamic educational institution that was founded in the 1970s. Additionally, the Madrasah is one of most influenced islamic education in Dero area. Madrasah Roudlotul Muttaqin is an education that focuses on learning Islam and morality. With more than 150 students, in this pandemic situation, the Madrasa is one of the concerns of the village government when carrying out the learning process that causes crowds. The various efforts made by administrators and clerics to make learning at Madrasah Didiyyah include: 1. utilizing and maximizing the online system 2. learning by implementing health protocols and 3. praying and praying to ask for Allah's protection to avoid the covid-19 outbreak. The conclusion of this study is that even in the pandemic situation that has not ended, Madrasah Diniyyah Roaudlotul Muttaqin continues to transform and innovate so that students can still get maximum religious and moral education.